МІСЦЕ ЦИФРОВИХ ТРЕНДІВ В СФЕРІ ГОТЕЛЬНО-РЕСТОРАННОГО БІЗНЕСУ - Fostolovych, Valentyna; Botsian, Tetiana (Zhytomyr Ivan Franko State University, 2022)
Business organization in the era of digital transformations has acquired a different expression and requires an innovative approach to each of the stages of its implementation. We can use SMM to inform a potential client about the emergence of a new idea, and to provide information about innovations, plans and forecasts. Social networks have become a tool of influence not only on human consciousness, but also on the technology of conducting business. The facts of physical isolation of contact between people due to the pandemic and military actions became not only a factor of oppression and destruction, but also a reason for changing the technology of communication in the social sphere and methodology in business activities. The traditional approach of marketing activities has changed to functioning in the online environment. The most effective trends in the social media marketing system of the company should be highlighted as micro-influencer marketing, artificial intelligence, agile marketing, voice search and live broadcasts and short video content. Equally important are quality service and the uniqueness and protection of data. By integrating these trends into the business, the company gets the opportunity to reach a new level of development. By applying modern marketing tools, thanks to the dissemination of quality information through the platforms of Instagram, Facebook and other social networks, we can multiply the number of visitors. Promotion of a trademark or brand of a restaurant or hotel in social networks is an effective, inexpensive tool that brings a quick level of payback. SMM trends help to find the target audience, spread information about the hotel and restaurant establishment and attract a real client, subject to compliance with the relevant quality service parameters. With the possession of technologies and tools in the field of SMM, the company can form its own business strategy for the year, using SMM tools it is possible to forecast trends, study and expand the target audience. The basis of modern business is its ability to be flexible to the changing needs of the consumer, which can be pursued most effectively through SMM.